Pengaruh Pemanfaatan Media Sosial, Kualitas Pelayanan dan Pengetahuan Penjual Terhadap Keputusan Pembelian Konsumen (Studi pada Peternakan Burung Perkutut Warna El Rozy Lampung) - Robi Santoso; Reni Diah Setiowati; Tri Endang Yulianti; Mustika Nurjanah (Jurnal Ragam Pengabdian, 2026)
The rapid advancement of digital technology has fundamentally transformed consumer behavior, particularly in the context of purchasing high-involvement products such as ornamental birds. This study aims to examine the influence of social media utilization, service quality, and seller knowledge on consumer purchase decisions at the El Rozy Lampung Color Dove Farm. A quantitative explanatory approach was employed, involving 200 respondents selected through purposive sampling from a population of 250 consumers. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The results indicate that social media utilization, service quality, and seller knowledge each have a positive and significant effect on purchase decisions both partially and simultaneously. Notably, seller knowledge emerged as the most dominant factor influencing consumer purchase decisions. The coefficient of determination (R²) of 0.551 reveals that these three variables collectively explain 55.1% of the variance in purchase decisions. These findings contribute to the marketing literature by highlighting the critical role of seller expertise in specialized markets and offer practical guidance for ornamental bird farms seeking to optimize their digital marketing strategies and service quality to enhance consumer trust and purchasing outcomes.